Defining, Describing, and Categorizing Public Health Infrastructure Priorities for Tropical Cyclone, Flood, Storm, Tornado, and Tsunami-Related Disasters. (9th March 2016) - Ryan, Benjamin J.; Franklin, Richard C.; Burkle, Frederick M.; Watt, Kerrianne; Aitken, Peter; Smith, Erin C.; Leggat, Peter
Abstract: Objectives: The study aim was to undertake a qualitative research literature review to analyze available databases to define, describe, and categorize public health infrastructure (PHI) priorities for tropical cyclone, flood, storm, tornado, and tsunami-related disasters. Methods: Five electronic publication databases were searched to define, describe, or categorize PHI and discuss tropical cyclone, flood, storm, tornado, and tsunami-related disasters and their impact on PHI. The data were analyzed through aggregation of individual articles to create an overall data description. The data were grouped into PHI themes, which were then prioritized on the basis of degree of interdependency. Results: Sixty-seven relevant articles were identified. PHI was categorized into 13 themes with a total of 158 descriptors. The highest priority PHI identified was workforce. This was followed by water, sanitation, equipment, communication, physical structure, power, governance, prevention, supplies, service, transport, and surveillance. Conclusions: This review identified workforce as the most important of the 13 thematic areas related to PHI and disasters. If its functionality fails, workforce has the greatest impact on the performance of health services. If addressed post-disaster, the remaining forms of PHI will then be progressively addressed. These findings are a step toward providing an evidence base to inform PHI priorities in the disaster setting. ( Disaster Med Public Health Preparedness . 2016;10:598–610)